PENGARUH ZAKAT PRODUKTIF TERHADAP PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH DAN KEBERLANJUTAN EKONOMI MUSTAHIQ DI BAZNAS KOTA CIREBON - Jefik Zulfikar Hafizd; Ahmad Khoirudin; Ahmad Faridz Anwar (IAIN Syekh Nurjati Cirebon, 2023)
AbstractZakat is a pillar of Islam that has a religious dimension as well as a social dimension. The utilization of zakat has an impact on increasing welfare. This study examines the effect of productive zakat on MSME empowerment and its influence on Mustahiq's Economic Sustainability at BAZNAS Cirebon City. This research uses mixed concurrent methods, namely combining qualitative and quantitative methods. The results of the study show that: 1) There is a positive and significant influence between productive zakat (X) on MSME empowerment (Y1) by BAZNAS Cirebon City with =3,6387 and =1,9997, it can be seen that > means variable X has a positive and significant influence on variable Y1; and 2) There is a positive and significant influence between productive zakat (X) on the economic sustainability of mustahiq (Y2) BAZNAS Cirebon City with =15.375 and =1.9997, it can be seen that > means that variable X has a positive influence on variable Y2. The results of the research prove that the hypothesis is accepted. The better the distribution of productive zakat, the better the quality of empowered MSMEs that support economic sustainability.Keywords: Productive zakat; MSME empowerment; Economic sustainability.